New combined method for low energy consumption in Wireless Sensor Network applications. (October 2018) - Chéour, Rym; Jmal, Mohamed Wassim; Abid, Mohamed
Over the past few years the applications for Wireless Sensor Networks (WSNs) have grown at an ever-increasing rate. However, the evolution of those networks has been reduced by the energy scarcity. It retards the development of the WSN performances required while exploring new applications and improving the WSN potential. Besides, in order to design energy-efficient solutions, it is important to take into account the power dissipation due to noncompliance with time constraints. As a result, we will provide a model of power management that will be simulated and validated by the STORM Simulator (Simulation TOol for Real time Multiprocessor scheduling). However, unlike traditional WSN energy management systems, our power manager reduces the energy consumption through a dual approach: a global and dynamic approach using the analysis of the behavior of the network and a local one applied at the node level. We have relied on energy optimization techniques to yield extensive lifetime for every node battery and mainly both Dynamic Power Management and Dynamic Voltage and Frequency Scaling, which are appropriate for the WSN. This model will be based on a global Earliest Deadline First scheduling policy. Besides, we aim to extend the STORM simulation tool to include those power management techniques.